A new species of Desmacella Schmidt, 1870 (Porifera, Demospongiae, Desmacellidae) from the Northeast region of Brazil - Nascimento, Elielton; Pinheiro, Ulisses (Zootaxa, 2022)
Desmacella is a Desmacellidae characterized by monactinal megascleres, arranged in plumose bundles; microscleres are sigmas and raphides; the latter may be absent (Hajud & Van Soest 2002). Thirty species are known worldwide, of which 19 occur in the Atlantic Ocean and three on the Brazilian coast: Desmacella annexa Schmidt, 1870; D. microsigmata, Cavalcanti, Santos & Pinheiro, 2015; D. tylovariabilis, Cavalcanti, Santos & Pinheiro, 2015 (de Voogd et al. 2022; Muricy 2022). In this paper, a new species of Desmacella from the Northeast region of Brazil is described. The material examined was compared with the descriptions and/or characterizations of all Desmacella species that occur in the Atlantic Ocean (Cavaltanti et al. 2015: 367–368). The specimen was preserved in ethanol 80% and is deposited in the Porifera Collection of the Natural History Museum of the Universidade Federal da Bahia.